Resilient Growth, Persisting Inequality : Identifying Potential Factors Limiting Shared Prosperity in the Dominican Republic - Galrão Carneiro, Francisco; Iwulska, Aleksandra; Reyes, José-Daniel; Sánchez-Martín, Miguel Eduardo (World Bank Group, Washington, DC, 2015)
The Dominican Republic (DR) has recorded exceptional growth over the past twenty years and has closed the gap with the Latin America and Caribbean (LAC) region. While in the early 1990s the DRs per capita income was only about 57 percent that in LAC, it has climbed to around 90 percent nowadays. However, the countrys ability to reduce poverty and improving equity has been less stellar. This note presents some stylized facts of the DR economy that might help understand this phenomenon. In doing so, the note addresses the following three questions: (i) Has growth been inclusive in the DR?; (ii) Why has the DR economy grown so rapidly?; and (iii) Why has growth not led to further improvements in equity? This note tentatively argues that some potential factors explaining the latter are the decline in real wages despite increasing productivity, special economic zones that are relatively isolated from the rest of the economy, and the States limited capacity for fiscal redistribution.